Characterization of isoforms of the serum amyloid A protein (SAA) superfamily - De Beer, Maria Cecilia (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.(Med.)) -- University of Stellenbosch, 1993.